Stimulus-driven and goal-driven effects on Pavlovian associative reward learning. Issue 2 (7th February 2018) - Bucker, Berno; Theeuwes, Jan
ABSTRACT: It has been shown that pure Pavlovian associative reward learning can elicit value-driven attentional capture. However, in previous studies, task-irrelevant and response-independent reward-signalling stimuli hardly competed for visual selective attention. Here we put Pavlovian reward learning to the test by manipulating the extent to which bottom-up (Experiment 1) and top-down (Experiment 2) processes were involved in this type of learning. In Experiment 1, the stimulus, the colour of which signalled the magnitude of the reward given, was presented simultaneously with another randomly coloured stimulus, so that it did not capture attention in a stimulus-driven manner. In Experiment 2, observers performed an attentionally demanding RSVP-task at the centre of the screen to largely tax goal-driven attentional resources, while a task-irrelevant and response-independent stimulus in the periphery signalled the magnitude of the reward given. Both experiments showed value-driven attentional capture in a non-reward test phase, indicating that the reward-signalling stimuli were imbued with value during the Pavlovian reward conditioning phases. This suggests that pure Pavlovian reward conditioning can occur even when (1) competition prevents attention being automatically allocated to the reward-signalling stimulus in a stimulus-driven manner, and (2) attention is occupied by a demanding task, leaving little goal-driven attentional resources available to strategically select the reward-signalling stimulus. The observed value-driven attentional capture effects appeared to be similar for observers who could and could not explicitly report the stimulus–reward contingencies. Altogether, this study provides insight in the conditions under which mere stimulus–reward contingencies in the environment can be learned to affect future behaviour.